The Influence of the Blended Learning Model and Student Activeness on Student Learning Outcomes in the Education Administration Study Program at Jambi University Post the Covid-19 Pandemic - Danola Padang, Astri; Sofyan, Sofyan; Hendra, Robi (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2024)
The aim of this research is to find out how influential blended learning and student activity are in increasing student learning outcomes. Blended learning is one solution to the weaknesses of online learning because it combines online, offline and face-to-face learning. Closing schools or universities is a solution to the post-Covid-19 pandemic which affects access to education, more than 370 million school children and students are not studying because of temporary closures and requiring them to study online or from home, but this learning makes students less active in learning due to network problems or other problems that make them feel dissatisfied with the learning model. Indonesia is one of the countries infected with the Covid-19 virus. In this case, as an effort to break the chain of spread of Covid-19, many schools or universities have been closed.